Investigating Fundamental Football Skills of Extracurricular Athletes - Sahrizan, Rahmat; Suwirman, Suwirman; Arsil, Arsil; Arnando Nando, Muhammad (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This investigation aimed to ascertain the baseline proficiency in fundamental football skills among a cohort of student-athletes (n=20) actively participating in the extracurricular football program at SMA Negeri 1 Sarolangun. Adopting a quantitative descriptive research paradigm, the current standing of essential football competencies was evaluated through the implementation of performance-based assessment protocols. These assessments specifically targeted key technical proficiencies, including passing-control, dribbling, shooting accuracy and power, and heading technique. Subsequent descriptive statistical analysis of the collected performance data revealed a "Moderate" mean proficiency level across the domains of passing-control, dribbling and shooting effectiveness. Conversely, the assessment of heading proficiency indicated a "Deficient" performance level within the studied group. Consequently, the composite evaluation of fundamental football skill execution demonstrated by the student participants enrolled in the SMA Negeri 1 Sarolangun extracurricular football program was determined to be at a "Moderate" overall level. These findings underscore the current skill distribution within the program and highlight a specific area, namely heading, requiring targeted pedagogical intervention to elevate the overall technical competence of the student-athletes. Further research could explore the underlying factors contributing to these proficiency levels and the effectiveness of specific training methodologies in addressing the identified deficiencies.